EFFECTS OF LIPOPROTEIN LIPASE ON THE STRUCTURE OF CHYLOMICRONS - Blanchette-Mackie, E. Joan (The Rockefeller University Press, 1973)
Chylomicrons isolated from rat lymph were complexed with lipoprotein lipase of post-heparin plasma (chylomicrons-LPL) in order to study the effects of lipolysis on the structure of chylomicrons. Triglyceride in the chylomicron core was readily hydrolyzed to free fatty acids (FFA) and glycerol when chylomicrons-LPL were incubated at pH 8.3 in medium containing albumin. Although most of the FFA were immediately released to the medium, some were retained within chylomicrons when FFA-binding sites on albumin were not available. These observations suggest that albumin may have a specific role in the transfer of FFA across the chylomicron surface film. Chylomicrons-LPL assumed many different shapes as they were depleted of triglyceride by the lipolytic action of the enzyme, and total removal of core triglyceride resulted in empty sacks of surface film. The surface film was visualized in sections of OsO(4)-fixed chylomicrons-LPL as a thin electron-opaque line, 25–30 Å wide, in areas where the underlying electron-opaque core had been replaced by zones of decreased electron opacity, and in folds of surface film extending outward from chylomicrons partially depleted of core lipid. The findings demonstrate that chylomicrons consist of a core of liquid triglyceride enveloped by a pliable and durable monolayer surface film, and that lipoprotein lipase reduces the triglyceride core without disrupting the surface film.